Nikah Mut'ah dalam Perspektif Hadis - Karlina Karlina (Holistic al-Hadis, 2018)
Discussion about Mutʻah marriage (Temporary Marriage) has been debated, both from Syiʻah and Sunni. The majority of Sunni opines it was originally permitted but then it was forbidden because of command of Khalifa ‘Umar Ibn al-Khaṭṭāb. There was a claim that the ban was happened in Khaibar war. While Syiʻah claims that Mutʻah Marriage is permitted until the last day (Judgment Day) and there is opinion claiming the marriage is not mansūkh (deleted). The example, the opinion of Ibn ‘Abbās revealing that verse 24 of surah An-Nisa is muhkamat and not deleted eventhough Ibn Baṭṭāl revealed that the people of Mecca and Yemen narrated that Ibn ‘Abbās forbade it. Based on the background above, the formulations of the problem are: 1. How is the hadith Mutʻah in the sight of Ibn Ḥajar Al-‘Asqalāniy? 2. How is the hadith Mutʻah in the sight of Muḥammad Baqīr Al-Majisi? The purpose of the research are: 1. Gaining an intensive, thorough and accurate understanding about Mutʻah Marriage from the two great muslim people Ibn Ḥajar Al-‘Asqalāniy and Muḥammad Baqīr Al-Majlisi teoriticallys, to give the answer of problem in this research. 2. Avoiding unreasonable and misguided fanatical attitudes from understanding both Sunni and Syiʻah. The method used in this research are library research method which collets data and information with the various of material then by using descriptive analysis method using Rijāl al-Ḥadith and Fiqh al-Ḥadith method. The results of this research are: 1. Ibn Ḥajar Al-‘Asqalāniy said in his lecture that Mutʻah Marriage was officially permitted and afterwards Rasūlullāh SAW forbade it at the time of Fatḥu Makkah and with the ḥadith writing off the statement that Mutʻah Marriage is permitted. 2. Muḥammad Baqīr Al-Majlisi said in his speech that Mutʻah Marriage is possible to do eventhough the ban was from Khalifa ‘Umar, while the permissibility of Mutʻah marriage is from Rasūlullāh (Prophet) and the command which comes from Alquran and done by the people of apostolic era.